Relationship between type 2 diabetes mellitus and coronary artery lesion characteristics: a single center study - Dubey, Laxman; Guruprasad, Sogunuru; Subramanyam, Gangapatnam (Nepalese Heart Journal, 2014)
Background: Coronary atherosclerotic burden is excessive in diabetic patients. The aim of present study was to assess the relationship between diabetes mellitus and plaque characteristics in patients with coronary artery disease. Methods: The coronary angiograms of 223 patients with significant obstructive lesions during April 2011 to May 2013 in College of Medical Sciences and Teaching Hospital were analyzed. The coronary lesions of patients with and without type 2 diabetes were compared. Results: 81 diabetic and 142 non-diabetic patients had significant coronary artery disease. Diabetic patients had more multivessel (64.2% versus 55.6%, p<0.05), and small vessel disease (74.1% versus 54.9%, p<0.05) than nondiabetic patients. Moreover, complex Type C lesion was significantly higher in the diabetic patients as compared to the nondiabetic patients (55.5% versus 29.6%, p<0.01). Conclusions: Complex coronary lesions were significantly more common in diabetic patients than in nondiabetic patients. Nepalese Heart Journal | Volume 10 | No.1 | November 2013| Pages 20-22 DOI: http://dx.doi.org/10.3126/njh.v10i1.9742